Relationship between allograft cyclosporin concentrations and P‐glycoprotein expression in the 1st month following renal transplantation. Issue 5 (6th March 2019) - Sallustio, Benedetta C.; Noll, Benjamin D.; Coller, Janet K.; Tuke, Jonathan; Russ, Graeme; Somogyi, Andrew A.
Abstract : The immunosuppressant cyclosporin is a P‐glycoprotein (P‐gp) substrate whose impaired function has been associated with an increased risk of cyclosporin‐induced nephrotoxicity following renal transplantation. This study investigated the relationship between blood and allograft cyclosporin concentration, and the effect of P‐gp expression. Fifty biopsy samples were obtained from 39 renal transplant recipients who received cyclosporin as part of maintenance immunosuppression. Blood cyclosporin concentrations (2 hours postdose) were obtained from clinical records, matching allograft cyclosporin concentrations were measured in frozen biopsy tissue by liquid chromatography–tandem mass spectrometry, and allograft P‐gp expression was assessed by immunohistochemistry. Blood and allograft cyclosporin concentrations in the 1st month post‐transplantation ranged from 505–2005 μg/L and 0.01–16.7 ng/mg tissue, respectively. Dose was the only significant predictor of allograft cyclosporin concentrations (adjusted R 2  = .24, F ‐statistic = 11.52, P  = .0019), with no effect of P‐gp expression or blood cyclosporin concentrations. P‐gp expression is not the major determinant of allograft cyclosporin concentrations.